Ejercicios de estimulación motriz en niños con distrofia muscular de Duchenne. - Maza Apuhango, Jhoanna Nataly (2024)
Introduction: Duchenne muscular dystrophy is an X-linked inherited disease that mainly affects boys, with a worldwide incidence of 1 case per 3500 live births. This pathology is characterised by progressive muscle weakness that begins in infancy, altering motor development; in advanced stages, they lose their ability to ambulate, and they even have respiratory complications. Motor stimulation exercises play a fundamental role in the development of children since they help to improve motor skills and mobility and counteract additional complications. Objective: To describe the functions of motor stimulation exercises in Duchenne muscular dystrophy for the prevention of delayed motor development in children, using scientific bibliographic sources. Methodology: The research was of bibliographic type; the information was collected from databases such as PubMed, Scopus, Cochrane Library, Dialnet, and Scielo. Seventy articles were found; through the inclusion and exclusion criteria, 25 articles were selected with a time period between the years 2019 and 2024. The same were evaluated according to the methodological scale PEDro with a score greater than 6. Conclusions: Motor stimulation exercises were shown to be crucial to improve motor skills and quality of life in children with DMD, but at the same time continued research is recommended to evaluate the efficacy of therapies and long-term treatment adherence.